Fatigue behavior prediction of welded joints by using an integrated fracture mechanics approach - Chapetti, Mirco Daniel (2012)
Current fracture mechanics methods for fatigue assessment of welded joints are based on long crack behavior. The present work introduces a method to predict the fatigue strength of welded joints by means of an integrated fracture mechanics approach (IFMA) that takes into account the fatigue behavior of short cracks. This methodology estimates the fatigue crack propagation rate as a function of the difference between the applied driving force and the material threshold for crack propagation, function of crack length. Firstly, the proposed fracture mechanic method is introduced and compared with the traditional fracture mechanic approach, used mainly for fitness for purpose assessment of welded joints with cracks or other crack-like defects. Then, the method is used for several theoretical and parametric applications to show its ability to predict the influence of different mechanical, geometrical and microstructural parameters in the definition of the fatigue resistance of welded joints. The influence of plate thickness, initial crack length and reinforcement angle on fatigue strength of butt-welded joints has been analysed and results show good agreement with experimental trends. Finally, the method is applied to predict and analyze the fatigue behavior of butt welded and non-load-carrying transverse fillet welded joints, and estimated and experimental results are analysed and compared.